Pelatihan Membuat Produk Kerajinan Kreatif dari Sampah Kantong Plastik - Yuliarty, Popy; Anggraini, Rini (University of Merdeka Malang, 2020)
Continuous use of plastic will use up some non-renewable natural resources. Besides it produces several substances which are harmful to human health. Utilization of plastic waste is an effort to reduce plastic waste to a minimum that can be done by recycling. The large number of plastic bag waste around the environment has led to the idea of â€‹â€‹using it into creative products that have artistic and economic value for residents around the campus. Based on this background, a problem arises. The lack of ability to recycle plastic waste into valuable products, therefore a movement needed to educate and provide skills to the community to recycle plastic waste. The purpose of this activity is to provide education and provide training to the environment around the campus, especially housewives and young women to recycle money into crafts from used plastic bags in the hope that it can reduce waste and generate new business opportunities, namely handicraft handicrafts from used plastic bags. Implementation of activities, namely providing counseling and practical skills to make products from plastic bag waste. The expected end result is awareness from the community about the dangers of using plastic bags and the skills to recycle used plastic bags.DOI:Â https://doi.org/10.26905/abdimas.v5i3.4912